The Consequences of Interest Rate Risk and Credit Risk on Profitability (Empirical Study on Banking Companies Listed on the Indonesia Stock Exchange) - Rumianti, Chaerunnisa; Chery T, Yoshia; Landa, Angelitha Natalia; Fernandes, Carlos; Anas, Muhammad Irfandi; Linthin, Olivia Nura (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to test and analyze the influence of interest rate risk and credit risk on profitability (empirical study of banking companies listed on the Indonesian Stock Exchange). The population in this study was 43 companies obtained using a purposive sampling method on Banking companies during the 2020-2022 period and based on predetermined criteria, a sample of 34 manufacturing companies listed on the Indonesia Stock Exchange was obtained. The total sample data for the 2020-2022 period is 102 samples. The analysis method used is multiple linear analysis with the help of SPSS software. The research results show that interest rate risk have a positive and significant effect on the profitability of banking companies listed on the Indonesian Stock Exchange in 2020-2022. And credit risk has a negative and significant impact on profitability in banking companies listed on the Indonesian Stock Exchange in 2020-2022.